2020
DOI: 10.1002/col.22534
|View full text |Cite
|
Sign up to set email alerts
|

The use of natural (Pinus pinaster) resin in the production of printing ink and the printability effect

Abstract: Alkyd resins are generally used in the production of printing inks. All industries look for alternative raw materials in the production of ink with the growing inclination toward using natural products. Resins forming the vehicle of the ink to be obtained from natural resources will provide benefits for the environment, nature, and living creatures. The aim of the study was to promote the use of natural resin in the ink system. Natural Pinus pinaster resin was added into vegetable and mineral oil-based solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, this presents a potential issue within the United States. In Europe, printers have broadly adopted polarized densitometric readings [5][6][7] which are not commonly found in the standard operating procedures in the US. 8 Introducing polarized densitometry into an environment where unpolarized densitometry is utilized can be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…However, this presents a potential issue within the United States. In Europe, printers have broadly adopted polarized densitometric readings [5][6][7] which are not commonly found in the standard operating procedures in the US. 8 Introducing polarized densitometry into an environment where unpolarized densitometry is utilized can be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…This maritime pine genus, which is geographically distributed, genetically diverse, and tolerant to ecological conditions, contains a large amount of resin (Çiçekler et al, 2018). Recent research has reported the use of various genus of pine resin in printing ink formulations, demonstrating the suitability of this renewable raw material (Hayta et al, 2020, 2021; Karademir et al, 2020). Throughout history, pine resin ( Pinus spp.)…”
Section: Introductionmentioning
confidence: 99%